Heat capacity of cylindrically confined helium: theoretical predictions versus experimental data - Chalyy, K.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2004)
Different systems which could exhibit size-dependent second-order phase transitions have beenstudied experimentally during the last quarter century. The validity of the proposed theoretical results is verified by comparing high-esolution experimental data with an analytical evaluation of the heat capacity of confined 4He. It is shown that the theoretical approach to the problem of the finite-size effect gives results that reasonably match the experimental data over a wide range of system sizes, from tens of nanometers up to a few micrometers for the cylindrical type of confinement geometry. The dependences of the shift of transition temperature on the cylinder size and boundary conditions are analyzed. The agreement of the results with finite-size scaling theory is confirmed.